Optimization of Bhabinkamtibmas Through Coaching and Counseling Activities to Prevent Theft with Aggravation at Pekalongan Police Station - Hutauruk, Henry Jonathan (Police Studies Review, 2024)
Theft with aggravation is the highest crime in the jurisdiction of the Pekalongan Regency Police Station. Frequent thefts are cattle theft and theft inside the house. Of course, the community is very restless because every year the crime of theft with aggravation is increasing. Therefore, the role of Bhabinkamtibmas is needed to provide coaching and counseling (Bimluh) to the community about theft with this incrimination. This guidance is carried out so the community understands how to secure their personal belongings and how to handle them if there is theft in their environment. This paper uses qualitative research methods with the type of field research. Then discuss the problem of optimizing coaching and counseling activities to prevent theft with aggravation. This writing uses management theory and concepts related to the focus of the problem in this final project. Data analysis in this study used the results of interviews, observations, FGDs, also document and data obtained from relevant sources. The result of this writing is that the main cause of the suboptimal implementation of Bimluh by the Bhabinkamtibmas Pekalongan Police Station is the lack of organizational resources and the implementation of Bimluh which is still not in accordance to Perkap number 21 of 2007. So it can be concluded that the implementation of guidance and counseling carried out by the Bhabinkamtibmas Pekalongan District Police has not been optimal due to inhibiting factors, both internal and external.